Synthesis of Vanadium Antimony Oxide Catalysts Via Slurry, Sol-Gel and Solid-State Methods - Razali, Mohd Asri (2004)
The influence of synthesis method on the formation of VSbO catalysts was examined. The syntheses applied in the present work were slurry, sol-gel and solid-state reaction method. The precursors obtained were further heated at various calcinations temperature; 673, 773 and 873 K and the dependence of the physicochemical characteristics of all the samples on the heat treatment imposed were also investigated. The synthesis conditions for the preparation of crystalline vanadium antimony oxide as mixed phases were found. Nitrogen physisorption at 77 K revealed samples prepared by slurry method gave higher Brunauer-Emmet-Teller (BET) surface area, SBET values compared to samples prepared by sol-gel and solid-state reaction methods. This was due to the chemical procedures done on the sample which promotes the formation of non-uniform particles with slit shaped particles compared to uniform particles formation displayed by other two methods. This phenomenon can be observed in Scanning Electron Microscopic, SEM micrograph. Upon heat treatment, SBET value decreased for all samples prepared by different method due to sintering effect. Nevertheless, the molar fractions of VSbO4 and -Sb2O4 phases depended on the heating temperature. As has been evidenced in X-ray Diffraction (XRD) analysis and Fourier Transform Infrared (FTIR) spectroscopy, higher calcination temperatures promote the formation of these two phases. The existence of the two phases which became dominant as the heating temperatures were gradually increased, are in accordance with reduced activities. Combination of transient kinetic studies; O2-Temperature Programmed Desorption, H2-Temperature Programmed Reduction and Temperature Programmed Reaction of propane, revealed the dependence of reducibility and catalyst activity with the relative intensity of VSbO4 rutile and -Sb2O4 phases. The VSbO samples were found to be increased in reduced activity as calcination temperature is increased. Temperature programmed reaction analysis suggested that the transformation of propane to acrylic acid are through the formation of intermediates propene and acrolein.